An Assessment and Correlation of Physical Activity and Mental Health Status of Medical Students - Khan, Huma; Saxena, Shashi; Khullar, Ujjwal; Mishra, Saurabh (National Journal of Community Medicine, 2019)
Background: As during the student life a doctor is usually young and somehow manages to cope with the stress of a becoming or being a doctor and ignores the importance of being physically ac- tive. But many times this casual approach towards their health comes in the form of various physical illnesses and psychological disorders. Globally, one in three adults is not active enough. For adults (18+): WHO recommends 150 minutes of moderate inten- sity activity per week. Objectives: 1. To assess the level of physical activity among medical students 2. To assess the mental health status of medical students. 3. To assess the correlation betweenphysical activity and the mental Health of medical students Sample size: The sample size was calculated by the formula: N= Z2PQ / d2, the final sample size calculated was 105 including both undergraduate and postgraduate students. Results: Out of 108 participants 101 (93.5%) were involved in an overall moderate intensity physical activity of more than 150 min- utes per week. The mean MET score found by our study is 76.3 MET/week. Overall 53 (49.1%) students were having psychologi- cal distress. Conclusion: A statistically significant association was found be- tween sitting or reclining for more than 8 hours and psychological distress.